Perilaku Kolom Beton Bulat Lilitan Spiral Pascabakar Akibat Beban Tekan Aksial Eksentris - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The objective of this research is to study the strength, stiffness, ductility, cracking patterns, and modes of failure of spirally reinforced concrete columns with circular cross section after fire subjected to eccentrically axial compressive loading. Six spirally reinforced concrete columns with circular cross section, having dimensions of 850 mm high and 160 mm diameter were tested under eccentric axial compressive loading with eccentricities of 120 mm and 150 mm. Among 3 specimens being tested at each eccentricity, 2 of them were exposed to fire, while the rest of them were not (represerting control specimen). The fire temperature was set to be 600Â°C and exposed up to 180 minutes. Six longitudinal steel reinforcements of 10 mm diameter were symmetrically placed in the circumference of the circular column section. Spiral reinforcements of 5 mm diameter with 40 mm spacing were used along the column. With load eccentricity of 150 mm, the maximum load capacity and stiffness of the column after fire, decreased 27,51% and 43,59%, respectively, compared to the column not exposed to fire. With load eccentricity of 120 mm, the maximum load capacity and stiffness of the column after fire decreased 18,43% and 18,53%, respectively, compared to the column not exposed to fire. Ductility of the columns after fire increased 10,09% and 45,69%, respectively, for the columns with the load eccentricity of 150 mm and 120 mm, compared to the columns not exposed to fire. Cracking patterns of the columns after and pre fire, in general, follows similar patterns of the spiral reinforcements at tension side of the columns. All columns exhibited modes of failure that were similar to the tension failure. The modes of failure was started by hairlines cracks appeared at tension side followed by the widening and elongating of several cracks as the load increased, and finally concrete spalled off from the concrete surface at compression side.